Use of split sample approach in evaluation of stochastic daily rainfall generation models - Aminuddin, Mohd. Baki, Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/